A modified hybridoma technique for production of monoclonal antibodies having desired isotypes - Napaporn Apiratmateekul (2018)
In the present study, we describe a modified hybridoma technique for production of monoclonal antibodies (mAbs) having a desired isotype. Mice were immunized with the antigen of interest. After having reached a high antibody titer, cells expressing IgM or IgG molecules were isolated from spleen cells of the immunized mice using a Magnetic Cell Sorting System. The isolated cells were fused with myeloma cells using the conventional fusion protocol. With the isolated IgM+spleen cells, more than 75% (85 ± 7%; means ± SD) were IgM producing cells and a large number of IgM mAbs specific to the protein of interest were obtained. With the isolated IgG+spleen cells, 41 ± 40% of the generated hybridomas produced IgG antibody and no IgM producing hybridoma was generated. A large number of IgG mAbs specific to the protein of interest could be produced. The results indicate that the generated hybridomas produce corresponding antibody isotypes as expressed on the surface of their starting cells. The technique that we have developed will be very useful for production of desired mAbs having a specific isotype. © 2009 Springer Science+Business Media B.V.